The association between early-life famine exposure and adulthood risk of thyroid diseases - Liu, Li; Yu, Liliang; Zheng, Daikun; Zhang, Dongmei; Liu, Lijun; Wan, Li; Shen, Yan; Cheng, Hongfeng (Frontiers in Nutrition, 2025)
BackgroundEarly-life exposure to famine is associated with an increased risk of various metabolic disorders. Nevertheless, evidence regarding its long-term effects on thyroid function and disease risk in older adulthood remains scarce. This study investigates the impact of fetal and childhood exposure to the Chinese Great Famine (1959–1961) on thyroid function and disorders in late life.MethodsThis cross-sectional study enrolled 1,956 participants who completed health examinations at a public hospital-based Physical Examination Center in Chongqing between 2022 and 2023. Based on birth cohorts, participants were stratified into three groups: the unexposed group (individuals born in 1963.1.1–1967.12.31), the fetal-exposed group (individuals born in 1959.1.1–1962.12.31), and the childhood-exposed group (individuals born in 1949.1.1–1958.12.31). Binary logistic regression models were used to evaluate the association between famine exposure and thyroid disease risk in later life. Multiple linear regression analyses compared thyroid function biomarkers between famine-exposed and non-exposed groups, adjusting for potential confounders.ResultsIn this study, 373 participants (19.1%) were exposed to the Chinese Great Famine during the fetal period, with 597 individuals (30.5%) experiencing childhood exposure. After adjusting for gender, smoking history, drinking history, dietary salt preference, current exercise status, educational level, body mass index (BMI), the fetal-exposed group demonstrated significantly elevated risks of both overt hyperthyroidism [OR = 4.36, 95% CI (1.02–18.71)] and subclinical hyperthyroidism [OR = 3.13, 95% CI (1.03–9.51)] compared to the non-exposed group. After adjusting for multiple comparisons using the Benjamini-Hochberg FDR method, fetal famine exposure maintained a statistically significant inverse association with thyroid nodule risk relative to childhood exposure [OR = 0.69, 95% CI (0.51–0.93)]. No significant associations were observed between famine exposure and hypothyroidism, thyroid autoantibody positivity, or autoimmune thyroid disorders. Notably, childhood-exposed participants exhibited higher thyroglobulin antibody (TgAb) levels versus non-exposed individuals [β = 40.30, 95% CI (2.21–78.40)].ConclusionFetal exposure to the Chinese Great Famine reduced thyroid nodule risk whereas childhood exposure increased TgAb levels, revealing distinct developmental windows for nutritional programming of thyroid health. These findings underscore the importance of timing in malnutrition-related thyroid dysfunction.